Nano Additives in Water Based Drilling Fluid for Enhanced-Performance Fluid-Loss-Control - ., Ali Samer Muhsan, Norani M Mohamed, Usman Siddiqui, Muhammad U S (2017)
Drilling fluid which is also known as drilling mud is a crucial element in oil and gas exploration process as it used to aid the drilling of boreholes into the earth. Among other functions, drilling fluid needs to carry drill cuttings to the surface of the well, support the walls of the well bore, provide hydrostatic pressure to prevent formation fluids from entering into the well bore, cool and lubricate the drill bit, prevent drill-pipe corrosion, facilitate the attainment of information about the formation being drilled, and create a thin low-permeability cake that protects permeable production formations. Water-based mud (WBM) is the most common drilling fluid used in oil industry. WBM is an expensive complex chemical system that is usually mixed with filtration-loss-prevention additives such as clay, lignite, or organic polymers, with bentonite clays being very common to control the fluid-loss during drilling process